2004
DOI: 10.1002/mrm.10686
|View full text |Cite
|
Sign up to set email alerts
|

Fat and water separation in balanced steady‐state free precession using the Dixon method

Abstract: The advantage of increased signal-to-noise ratio (SNR) efficiency in balanced steady-state free precession (SSFP) imaging (also denoted as true fast imaging in steady-state precession (TrueFISP), balanced fast field-echo (FFE), or fast imaging employing steady-state acquisition (FIESTA) by various manufacturers) has made this technique attractive for clinical applications. Examples of such applications include (but certainly are not limited to) cardiac imaging (1,2), angiography (3,4), gastrointestinal imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…Dixon techniques can be successfully implemented with many different pulse sequences, including fast spin echo (18,(45)(46)(47)(48), steady-state free precession (18,49), or even non-rectilinear (50,51) pulse sequences. However, the success of most Dixon techniques is in general dependent on the success of phase correction.…”
Section: The Data Acquisition Strategy and Other Considerationsmentioning
confidence: 99%
“…Dixon techniques can be successfully implemented with many different pulse sequences, including fast spin echo (18,(45)(46)(47)(48), steady-state free precession (18,49), or even non-rectilinear (50,51) pulse sequences. However, the success of most Dixon techniques is in general dependent on the success of phase correction.…”
Section: The Data Acquisition Strategy and Other Considerationsmentioning
confidence: 99%
“…Another clinical study reported significant improvement in image quality using respiratory navigator-gated bSSFP NCE-MRA instead of the breath-hold approach (93). The Dixon method bSSFP, where two bSSFP images acquired with different center frequency offsets are combined using the Dixon method (94), has been demonstrated to depict conspicuous vessels with good fat suppression for NCE-MRA in renal arteries (95) and arteries of the extremities (96). Also leveraging the frequency selectivity of bSSFP, fat-suppressed bSSFP NCE-MRA can be used in conjunction with an alternate TR bSSFP technique to reduce fat signal to image the arteries in the lower extremities (97).…”
Section: Applicationsmentioning
confidence: 99%
“…Our method improves on conventional Dixon methods (Glover, 1991;Huang et al, 2004;Reeder et al, 2004;Vasanawala et al, 2000) since it − does not dictate a particular configuration of phases (e.g., in and out of phase) and look for pulse-sequence design variables to match this configuration, − takes all tissue parameters into account (relaxation constants, as well as resonance offset),…”
Section: Advantages Of the Proposed Methods Of Quantificationmentioning
confidence: 99%